CULTURAL ASPECTS OF TRANSLATING ENGLISH PHRASEOLOGICAL UNITS INTO UZBEK - Mahliyo Oymirzayeva, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This paper examines the cultural challenges and strategies involved in translating English phraseological units into Uzbek. Phraseological units—such as idioms, proverbs, and fixed expressions—often carry meanings deeply rooted in cultural contexts, historical events, and social norms. The study analyzes examples where direct translation fails to convey intended meanings, leading to potential misunderstandings or loss of nuance. It explores methods like cultural adaptation, descriptive translation, and the search for functional equivalents in Uzbek to preserve both meaning and stylistic effect. The paper highlights the importance of cultural competence for translators and underscores how linguistic creativity can bridge gaps between English and Uzbek cultures, ensuring accurate and culturally sensitive translations.